2010
DOI: 10.1007/s15010-010-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-interferon-γ autoantibody and opportunistic infections: case series and review of the literature

Abstract: Immune defects in interleukin-12-dependent interferon-gamma (IFN-γ) pathways are associated with disseminated infections caused by non-tuberculous mycobacteria (NTM) and Salmonella. Recently, there have been an increasing number of reports of acquired autoantibodies to IFN-γ in adults, especially in Asian patients. We describe here three human immunodeficiency virus-negative Thai adults who had persistent or recurrent disseminated infections caused by NTM, Salmonella, and other opportunistic pathogens, possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 19 publications
5
75
1
Order By: Relevance
“…2,3,5,[18][19][20][21][22] Patient 2 had a slightly decreased CD4 lymphocyte count but not low enough to cause disseminated nontuberculous mycobacterial disease. All patients had been healthy into adulthood, whereas primary immunodeficiencies tend to present early in life.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,[18][19][20][21][22] Patient 2 had a slightly decreased CD4 lymphocyte count but not low enough to cause disseminated nontuberculous mycobacterial disease. All patients had been healthy into adulthood, whereas primary immunodeficiencies tend to present early in life.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, high levels of certain anticytokine antibodies (e.g., anti-granulocyte-macrophage colony-stimulating factor [GM-CSF] antibodies) were associated with cryptococcosis in HIV-negative patients (276). These antibodies predispose individuals to opportunistic infections by impairing innate immunity and may be especially relevant among HIV-negative patients in Asia (277,278). Saijo et al most recently reported the presence of anti-GM-CSF autoantibodies in the plasma of seven apparently immunocompetent patients with C. gattii meningoencephalitis but, interestingly, not in the plasma of patients with C. neoformans disease (279).…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 99%
“…Negative changes in a positive control are caused by individual background factors, such as an immunocompromised status, including acquired immunodeficiency syndrome or immunosuppressant intake. The level of anti-IFN-γ autoantibodies, as reported in severe infectious diseases, including sepsis caused by opportunistic pathogens (18) or disseminated nontuberculous mycobacterium infection (19,20), is also high in this situation.…”
Section: Discussionmentioning
confidence: 77%